2020
DOI: 10.3390/microorganisms8071027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Probiotic Combination in InR[E19]/TM2 Drosophila melanogaster on Longevity, Related Gene Expression, and Intestinal Microbiota: A Preliminary Study

Abstract: The insulin receptor (InR) pertains to the insulin receptor family, which plays a key role in the insulin/insulin-like growth factor (IGF)-like signaling (IIS) pathway. Insulin signaling defects may result in the development of metabolic diseases, such as type 2 diabetes, and the InR mutant has been suggested to bear insulin signaling deficiency. Numerous studies have reported that probiotics are beneficial for the treatment of diabetes; however, the effect of probiotics on patients with InR deficiency has sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 85 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Untreated flies showed the normal NGR decline, while only one week of LGG or IAB exposure helped maintain climbing behaviors ( Figure 5 B, Supplementary Table S4A ). Longevity studies also revealed that early IAB treatment (one week, 1:800) promoted longevity, while middle-aged flies treated with either biologic had increased lifespans ( Figure 5 C, Supplementary Table S4B ) [ 3 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Untreated flies showed the normal NGR decline, while only one week of LGG or IAB exposure helped maintain climbing behaviors ( Figure 5 B, Supplementary Table S4A ). Longevity studies also revealed that early IAB treatment (one week, 1:800) promoted longevity, while middle-aged flies treated with either biologic had increased lifespans ( Figure 5 C, Supplementary Table S4B ) [ 3 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that even modest OS level changes, including the production of reactive oxygen/nitrogen species, can further exacerbate inflammation in the neural tissues [ 13 , 15 , 16 , 17 ]. Indeed, elevated OS levels, cytokine imbalances, and glial activation can further damage neural tissue, accelerating neurodegenerative disease [ 18 , 19 , 20 , 21 , 22 ]. Identifying treatments that lower OS levels and promote cellular homeostasis would be beneficial for a range of maladies related to ageing or progressive cellular damage ( Supplementary Figure S1A,B ) [ 13 , 16 , 17 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In aging rats, probiotics modulate AMPK activity and prevent telomere shortening [ 116 ]; protect aging bone and muscle [ 117 ]; and improve lipid, renal, and liver profiles, while also inhibiting the growth of pathogens Escherichia coli , Staphylococcus aureus , and Staphylococcus epidermidis [ 118 ]. However, in wild-type Drosophila melanogaster, although a probiotic mixture increases mean and median lifespan, it decreases mean and median lifespan in Drosophila melanogaster with insulin receptor deficiency and a type 2 diabetes mellitus phenotype [ 119 ]. These preliminary studies suggest that although probiotics may impact pathways involved in longevity, they may not universally prolong lifespan, and thus, more work is required to distinguish factors associated with the utility or possible harm of probiotics.…”
Section: Interventionsmentioning
confidence: 99%